Altruisme dalam Novel Hati Suhita Karya Khilma Anis Berdasarkan Teori Strukturasi - Miolo, Syahrul Alfitrah (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2024)
When an individual socializes with other individuals, sometimes he only cares about himself. However, some individuals prioritize other people and are even willing to sacrifice themselves, when socializing with other individuals. This research aims to analyze altruism in the novel Hati Suhita by Khilma Anis using the structuration theory initiated by Anthony Giddens. In this research, researchers used qualitative descriptive methods. In collecting data, the researcher read the novel Hati Suhita carefully, then the researcher determined the actions and awareness of the agents (characters) in the novel. Next, the researcher analyzed the data that had been collected by identifying the discursive awareness, practical awareness, and unconscious motivation of the characters in the novel. After that, the researcher compared the results of this research with the results of other research which analyzed a novel using Anthony Giddens structuration theory. Then, the researcher draws conclusions based on the data that has been collected and analyzed by the researcher. The results of this research show that the altruism in the novel Hati Suhita is depicted by agents through their actions. Their actions are based on three consciousnesses, namely discursive, practical, and unconscious motivation. The results of this research also show that the structure of the novel Hati Suhita greatly influences the agent. However, the agent in the novel Hati Suhita is unable to influence the existing structure.